Predictors of intention to quit smoking among hospital male staff - Sajjad Narimani; Rabiollah Farmanbar; Ehsan Kazemnejad Leyli (Gonabad University of Medical Sciences, 2017)
Smoking is the most preventable cause of premature death in the world. And its disadvantages imposes heavy financial burden on the health system. Due to the great advances in health education, health care approach to identify factors associated with smoking cessation changed and models of health education emphasized, and most useful of them are transtheoretical model (TTM). This study examined predictors of smoking cessation among male staff in the hospitals. This study included a convenience sample of 200 current and former smokers staff employed at four hospitals. The instruments included decisional balance scale, self-efficacy scale, processes of change scale (behavioral and experiential), and stages of change which self-reportly completed. The results showed that 66.5% of participant were located in earlier stage of change, self-efficacy and processes of change and decisional balance significantly correlate with stage of change, and experiential processes of change (β=0.067), self-efficacy (β=-0.059) and behavioral processes (β=0.027) were the strongest predictor of stage of change respectively. The results revealed that increases in readiness to quit smoking were significantly predicted by mechanisms of self-efficacy and experiential process of change such as environmental reevaluation and behavioral process of change such as stimulus control and counter conditioning, which can lead to positive progress in stage of change in smokers. These results support the application of TTM for smoking cessation interventions and indicate that the procedure was very effective in improving intention to quit smoking among hospitals staff.